(3CacGQ GdCacGQ aj GdCOHjGJ hGdCTYGQs - (3YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, CHh MaU, Rjf GdOjf GHf GdhQOj GdeYQj GdcfOj,J (B749 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPj GdMeO ef aVdg hHYO(B: (3ajbhd GdabjQ, GdeYJQa HGdJbWjQ, s
(3BNQgG (B:s
(3hJZjjQ eG YhOJfG ef fYeI YhOJfG efc GdcKjQ GdWjHG Ke GdUdGI Ydi GdfHj hBdg hUMGHg hGdZQ ef Cgd GdYHG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B228 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B3s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B49 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs